A Time to Pause and Ponder - Christopher Spencer; Peer S. Daugbjerg (European Teacher Education Network, 2018)
In this paper the authors share experiences from teacher education in the UK and Denmark. They apply methodologies for supporting teacher students from initial exposure to the classroom setting, through training programmes and into the early stages of their professional work. They use Frankl's notion of meaning making through encountering and doing deeds as eminent ways of creating meaning in education. They demonstrate how two similar but also different methods i.e. narrative inquiry and self- study can create basis for exposing meaning-making among teacher students and teacher educators. They conclude that within education meaning is created in the engagement with the world and the persons inhabiting this world.